Role of Cytokines (IL-17 & IL-33), FGF-18, and WNT-5 in the Pathogenesis of Patients with Established Type II Diabetes - Mohammed, Przha Fadhil; Amin, Kawa Abdulla M. (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Biomarker investigation is important to detect the presence/severity of hyperglycemia, implying diabetes/pre-diabetes, or over time, as a risk factor for diabetic retinopathy, nephropathy, and other vascular complications related to diabetes. Objectives: To determine the role and level of certain cytokines, FGF-18, and WNT5A in the serum of diabetic patients. Patients and Methods: A case-control comparative study was conducted on 50 healthy individuals and 100 diabetic patients. Then; a validated questionnaire was used to collect the participants’ data. Next, participants’ serum level of IL-17, IL-33, FGF-18, and WNT5A was determined using the ELISA technique and the blood level of glycated hemoglobin (HbA1C). Results: A highly significant difference in the levels of HbA1C and FGF-18 and a significant difference in levels of IL-17 and IL-33, with no significant difference in WNT-5A level, were seen between the studied groups. There was no significant difference between the biomarkers level and each gender, age, BMI, and duration of DM in the patients (p>0.05). A positive correlation was observed between the number of symptoms in the patients and levels of IL-17 (p=0.003) and IL-33 (p=0.018). Also, a positive correlation between IL-17 and IL33 (Rho=0.874, p<0.001), IL-17 and FGF-18 (p=0.023), as well as between IL-33 and FGF-18 (p=0.041) were seen. Conclusion: It is realized that IL-17, IL33, and FGF-18 expression are directly related to DM, Additionally, a positive correlation between most biomarkers was seen. The detection of the cytokines’ levels and their relations with diabetic will affect the diagnosis, knowledge about the disease immunology, and thereafter effects on the treatments of patients with diabetic depending on our findings.
Keywords: Biomarkers; diabetes mellitus; pathogenesis; case control comparative study; correlations